PERANAN ALOKASI DANA DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR DESA MATAWINE TAHUN 2018-2020 - Halimudin Halimudin; Abd Azis Muthalib; Yohane Boni (JEP (Jurnal Ekonomi Pembangunan), 2021)
The results of this study show that the variable allocation of village funds plays a role in the variables of infrastructure development in Matawine Village of Lakudo District of Central Buton Regency, this can be seen from the infrastructure development carried out to increase from previous years. This is in line with the increase in the amount of Village Fund Allocation received by Matawine Village. Then in infrastructure development that is done can already contribute to the improvement of community welfare and economic improvement of the community because in the planning process carried out the community is always involved so that the development carried out in accordance with what the community wants and needs and in the implementation of society is also involved as a workforce and this becomes additional income for the community.